G-protein coupled receptor kinase-2 regulates the migration of chronic lymphocytic leukaemia cells to sphingosine-1 phosphate in vitro and their trafficking in vivo - María Chiara Cassarino; Ana Colado; Valeria Sarapura Martinez; Claudio Martines; Alice Bonato; Martin Bertini; Miguel Pavlovksy; Rosario Custidiano; Fernando Raimundo Bezares; Pablo Elías Morande; Mónica Vermeulen; Romina Gamberale; et al. (Scientific Reports)
Abstract Disease progression and drug resistance in patients with chronic lymphocytic leukaemia (CLL) depend on signals from the tumour microenvironment in lymphoid sites. GRK2 inhibits the egress of normal B cells from lymphoid tissues by inducing the downregulation of the S1P-receptor 1 (S1PR1). In this study we investigated the role of GRK2 in the context of CLL using in vitro and in vivo murine models, and also primary samples from CLL patients. We found that pharmacological inhibition of GRK2 enhanced the migration of leukemic cells from CLL patients towards S1P and impaired the S1P-induced downregulation of S1PR1. Likewise, CRISPR/Cas9-mediated GRK2 deletion in a murine leukemic cell line derived from the Eµ-TCL1 mouse model of CLL also increased migratory capacity toward S1P in vitro. Furthermore, when injected into mice, GRK2-deficient murine leukemic cells exhibited an altered in vivo localization, with a higher presence in the blood and spleen compared to the bone marrow. Within the spleen, these cells displayed reduced localization to the follicles compared to control murine leukemic cells. Deletion of GRK2 on murine leukemic cells did not affect their in vitro proliferation, but notably, conferred a growth disadvantage in vivo. These findings underscore GRK2 as a critical regulator of the localization of CLL cells in vivo and suggest its potential as a therapeutic target to disrupt survival niches in CLL.